Butterflies in the Gardens: the Fate of Van Groenendael's Collection - Miracle, Eulàlia Gassó (Studium, 2019)
During WWII, hundreds of thousands of butterflies found refuge in the Botanical Gardens in Bogor. The specimens belonged to Jan van Groenendael, a physician who lived and worked in Java and Flores between 1931 and 1954, together with his wife Adriana Krijger. The collection is of great scientific value, but as it is always the case with natural history collections, it is also an interesting subject for historical studies. The collection has a comprehensive archive attached to it, including journals, photographs, letters ethnographical and entomological articles. Taken together, this material takes us into the life of the Van Groenendaels in Indonesia through the 1930’s, WWII and the decolonisation period. This paper offers a glimpse of their compelling story: a tiny sample of the knowledge hidden in the Van Groenendael collection - butterflies and archives - for both biologists and historians.